Uji Karakteristik Nyala Api Menggunakan Metode Pembakaran Droplet Pada Bahan Bakar Diesel Dengan Penambahan Biodiesel Kesambi - Prasetiyo, Dani Hari Tunggal; Abdillah, Hartawan; Wahyudi, Djoko; Muhammad, Alief; Baihaqi, Mas Ahmad (TURBO [Tulisan Riset Berbasis Online], 2023)
Population growth and rapid technological developments cause the need for energy to increase. Energy needs are more dominated by fossil sources, especially petroleum. However, the level of utilization of energy from fossil sources does not allow it to last long, this is because fossil energy sources have limitations. Therefore it is necessary to use alternative energy sources, one of which is biodiesel. Biodiesel can be obtained from plants. One type of plant that can produce biodiesel is the kesambi plant. However, before it is mass-produced and used in transportation and industrial machinery, it needs to be tested first. One of them is the combustion test with the droplet method. In this study, a droplet combustion test was carried out using diesel fuel by mixing kesambi biodiesel. The results showed that pure diesel fuel produced the highest temperature and the fastest ignition delay time. The high flame on diesel fuel is also the highest. However, the duration of the ignition lies in the composition of pure biodiesel fuel without mixture.